Upaya Pencegahan Radikalisasi Dini pada Siswa Melalui Program Unggulan di SDNU Metro Barat Tahun Akademik 2019/2020 (Aspek Ideologi Beragama dan Sosial) - Masrurotul Mahmudah; Muhammad Ngali Zainal Makmun (AR-RIAYAH: Jurnal Pendidikan Dasar, 2020)
In the current stage of development has an impact on the development of human thought patterns on the attitude of individual religiosity. So there is an abuse of religious principles and has been widely applied to children with the lure of jihad fi sabilillah and fighting in the way of Allah guaranteed heaven. Therefore in this study raised a problem, namely: Why should there be efforts to prevent early radicalization in students through excellent programs at SDNU Metro Barat Academic Year 2019/2020 (aspects of religious and social ideology) ?. The research is descriptive analysis with two approaches namely ideological and social. In extracting data by interview, observation and documentation. While the validity of the data uses data triangulation. From data collection and data analysis, it can be seen that the importance of efforts to prevent early radicalization in SD NU Metro Barat has a superior program is to strengthen religious ideology understanding in children / students, so as to minimize the occurrence of doctrination related to radicalism under the guise of reward and heaven